Improved structural design of single- and double-wall MnCo2O4 nanotube cathodes for long-life Li–O2 batteries. Issue 27 (2nd July 2018) - Wu, Haitao; Sun, Wang; Shen, Junrong; Lu, Chengyi; Wang, Yan; Wang, Zhenhua; Sun, Kening
Abstract : MnCo2 O4 nanotubes with a tunable structure are fabricated by electrospinning and serve as bifunctional catalysts for Li–O2 batteries with significantly improved performance. Abstract : Developing a cathode material with a stable pore structure and efficient bifunctional activity toward oxygen electrochemistry is the key to achieve practical and high-performance Li–O2 batteries. Here, hierarchically porous MnCo2 O4 nanotubes with single- or double-wall architecture are fabricated through a facile electrospinning technique, by adjusting the concentration of the electrospinning solution. The electrochemical measurements indicate that both types of nanotubes possess excellent catalytic abilities toward oxygen reduction and evolution reactions in alkaline aqueous or non-aqueous media. When used as air-electrode catalysts for Li–O2 batteries, both single- and double-wall MnCo2 O4 nanotubes show significantly improved electrochemical performance. In particular, the novel double-wall MnCo2 O4 nanotubes (DW-MCO-NT), with a high surface area and a large pore volume almost twice as big as the single-wall nanotubes, can offer numerous catalytically active sites as well as sufficient space to deposit discharge products. The DW-MCO-NT based Li–O2 batteries can deliver a maximum discharge capacity of 8100 mA h g −1, with a potential plateau at 2.77 V, and achieve an excellent cyclability over 278 cycles, under strict conditions of 1000 mA h g −1 at 400 mA g −1 within 2.6–4.3 V. Moreover, the XRD and SEM analyses show that the dominant discharge product with a particulate shape is crystal Li2 O2 and is prone to being completely decomposed, endowing the MnCo2 O4 nanotube-based Li–O2 battery with a long cycle life.